A day in the life of a dolphin: Using bio‐logging tags for improved animal health and well‐being. Issue 3 (2nd June 2017) - Alex Shorter, K.; Shao, Yunli; Ojeda, Lauro; Barton, Kira; Rocho‐Levine, Julie; van der Hoop, Julie; Moore, Michael
Abstract: Little quantitative information on the behavior, health, and activity level of managed marine mammals is currently collected, though it has the potential to significantly contribute to management and welfare of these animals. To address this, high‐resolution motion‐sensing digital acoustic recording tags (DTAGs) collected data from animals under human care ( n = 5) during their daily routine, and classification algorithms were used for gait analysis and event detection. We collected and examined ~57 h of data from five bottlenose dolphins ( Tursiops truncatus ). Day‐scale changes in behavior and activity level were observed and diurnal changes were detected with lower activity at night ( n = 1). During the day, animals spent about 70% of their time swimming. The deepest part of the lagoon is ~3 m and individual dives were typically shallow (~1 m) with the dolphins tending to utilize a fluke and glide gait pattern. Activity level was quantified using overall dynamic body acceleration. A significant relationship between normalized activity level and glide duration during different portions of the dive was measured; animals fluked more during descent and glided more during ascent. This could indicate that even during very shallow dives the dolphins use their positive buoyancy to improve energy economy.